Influence of Body Composition on Gait Kinetics throughout Pregnancy and Postpartum Period - Marco Branco; Rita Santos-Rocha; Filomena Vieira; Maria-Raquel Silva; Liliana Aguiar; António P. Veloso (Scientifica)
Pregnancy leads to several changes in body composition and morphology of women. It is not clear whether the biomechanical changes occurring in this period are due exclusively to body composition and size or to other physiological factors. The purpose was to quantify the morphology and body composition of women throughout pregnancy and in the postpartum period and identify the contribution of these parameters on the lower limb joints kinetic during gait. Eleven women were assessed longitudinally, regarding anthropometric, body composition, and kinetic parameters of gait. Body composition and body dimensions showed a significant increase during pregnancy and a decrease in the postpartum period. In the postpartum period, body composition was similar to the 1st trimester, except for triceps skinfold, total calf area, and body mass index, with higher results than at the beginning of pregnancy. Regression models were developed to predict women’s internal loading through anthropometric variables. Four models include variables associated with the amount of fat; four models include variables related to overall body weight; three models include fat-free mass; one model includes the shape of the trunk as a predictor variable. Changes in maternal body composition and morphology largely determine kinetic dynamics of the joints in pregnant women.